Symbolic Values and Meanings in Lasem Batik Motives - Novia Dyah Mahesti; Eko Sugiarto; Rahina Nugrahani (Universitas Negeri Semarang, 2023)
Every batik motive has an interesting philosophy, as well as the Lasem batik motive. The Lasem batik motive also contains an interesting philosophy. This study aims to analyze the value and symbolic meaning contained in Lasem batik motives. This study uses a qualitative method by describing the object under study and using a semiotic approach. The dominant motives of Lasem written batik are Hong Bird, Gunung Ringgit, Dragon, Seruni, Latohan, Kricakan, Brayo, Gurdha and Lokcan motives. The Hong Bird motive means noble beauty and intelligence and has the value of effort and hard work. The Gunung Ringgit motive means abundant fortune and has the value of effort and hard work. The Dragon motive means strength and beautiful hope and has a strength value. The Seruni motive means well-being in old age, happiness and longevity, and has a value of beauty and harmony. The Latohan motive is a symbolic form of the latohan plant and has a natural wealth value. The Kricakan motive is a symbolic form of the construction of the Anyer-Panarukan road and has the value of hard work. The Brayo motive is a symbolic form of the Brayo plant and has natural wealth values. The Gurdha motive means valor, protection and fortitude and has heroic value. The Lokcan motive means love for fellow human beings and has a value of love.